The importance of high school on the university students’ success in the subject of mathematics - Lubishtani, Feride Qorrolli; Avdylaj, Blerina Tafolli (Frontiers in Education, 2023)
This research examines the relationship between high school, namely, high school profiles, and students’ success during an elementary mathematics course at university. For the analysis of this relationship, a mixed methods case study was chosen as the research design. The instruments for collecting the data were a questionnaire and a semi-structured interview that provided answers to the research questions. The sample consisted of 81 students (N = 81) from the University of Applied Sciences in Ferizaj, Kosovo, who participated in the questionnaire, and 12 out of the 81 students were also interviewed. The research results indicated that a positive, not strong, correlation exists between high school and university success. Moreover, students expressed that knowledge gained in high school made them feel sufficiently prepared during the lectures on elementary mathematics. The high school profile makes a difference in the students’ success in the elementary mathematics course at the university.